A survey of reporting of colorectal cancer in Scotland: compliance with guidelines and effect of proforma reporting. Issue 6 (24th February 2014) - Woods, Y L; Mukhtar, S; McClements, P; Lang, J; Steele, R J; Carey, F A
Abstract : Aims: The main purpose of the study was to present a baseline audit of reporting of colorectal cancers resection specimens in Scotland, audited against the Royal College of Pathologists (RCPath) standards (2007) and NHS Quality Improvement Scotland (NHS QIS) standards. Methods: 50 consecutive rectal and 50 consecutive colonic cancer cases from 2011 were audited from 10 Scottish health boards involved in colorectal cancer reporting (n=953). The rates of reporting of serosal involvement, extramural venous invasion (EMVI) and the mean numbers of lymph nodes found were audited against RCPath standards and compared between units that routinely used a reporting proforma versus those that did not. Results: The performance in reporting of rectal cancer was generally worse than for colonic cancer, with only three units meeting the RCPath standards for reporting of rectal cancer. There were significant differences between units that routinely used a proforma, with the non-proforma group failing to meet the minimum standards for both serosal involvement (6%) and EMVI (24%). In the non-proforma group, 56% of rectal cases had a mean lymph node count of 12 or more compared with 81% in the proforma group. Conclusions: Significant differences exist in the frequencies with which important adverse prognostic features are reported by pathologists across 10 Scottish health boards. This has potential implications for patient care. Health boards that make routine use of reporting proformas are more likely to meet RCPath guidelines for reporting of these important pathological parameters.